Intestinal injury and changes of the gut microbiota after ischemic stroke - Shen, Yang; Wang, Jin; Li, Yina; Kang, Xianhui; Gu, Lijuan (Frontiers in Cellular Neuroscience, 2025)
Stroke is the second leading cause of death and the third leading cause of disability worldwide, with ischemic stroke (IS) accounting for the vast majority of cases. This paper reviews the latest research on intestinal damage, changes in the gut microbiota, and related therapeutic strategies after IS. Following IS, the integrity of the intestinal mucosal barrier is compromised, leading to increased intestinal permeability. The gut microbiota can translocate to other organs, triggering systemic immune responses that inhibit recovery after IS. Moreover, the composition and proportion of the gut microbiota change after IS. The number of beneficial bacteria decreases, whereas the number of harmful bacteria increases. The production of beneficial metabolites, such as short-chain fatty acids (SCFAs), is reduced, and the levels of harmful metabolites, such as trimethylamine N-oxide (TMAO), increase. Antibiotics after IS not only help prevent infection but also have neuroprotective effects. Although poststroke reperfusion therapy can effectively restore cerebral blood flow, it may also cause intestinal mucosal damage and gastrointestinal dysfunction. Nutritional support after IS can alter the gut microbiota structure and promote neurological recovery. Therefore, individualized treatment for IS patients is crucial. In summary, IS affects not only the brain but the entire body system, especially the gut. Intestinal damage and dysbiosis are critical in IS occurrence, development, and prognosis. By protecting the intestinal mucosa and modulating the structure of the gut microbiota, intestinal damage and related infections can be reduced, improving patient prognosis. Future research is needed to explore therapeutic methods targeting the gut microbiota, providing more comprehensive and effective treatment strategies for IS patients.